FRI0096 The association between migraine and antiphospholipide antibody in systemic lupus erythematosus. (1st June 2001) - Appenzeller, S; Costallat, LT; Coimbra, IB; Bertolo, MB; Samara, A
Abstract : Background: Various neurological manifestations have been considered to be important features of Systemic Lupus Erythematosus (SLE) and indicative of Central Nervous System (CNS) involvement. Few studies of SNC include headache and the real prevalence of headache in SLE remain unknown, but some authors consider it one of the most frequent neurological symptoms, especially during acute disease. Objectives: To determine the point prevalence and the different types of headache in patients with SLE. To investigate associations between headache and clinical and laboratory manifestation of SLE, corticosteroid therapy, disease activity and CNS involvement. Methods: A cross-sectional study of 40 patients with SLE was compared to 40 patients with rheumatoid arthritis (RA) and 40 controls. To assess the different types of headache an especial questionnaire was elaborated, according with ACR case definition. Systemic disease activity was measured by SLEDAI. Statistics were performed by chi-square test and by Fisher's exact test. Results: Headache was observed in 62.5% in SLE compared to 47.5% (p = 0.26) in RA and to 35.1% in controls (p = 0.0247). The types of headaches observed in SLE was migraine in 46%, tension headache in 36% and 20% had headaches during their menses. In RA we observed that 15.7% (p = 0.05) had migraine, 21% had tension headache, 37.5% had headache related to visual problems and 26% had headaches during the menses. In the control people group the prevalence of migraine was 23% (p = 0.05), tension headache 38% and headache during the in 38%. There was no significant association between headache and clinical manifestations of SLE, with laboratory abnormalities or the use of corticotherapy. A significant association in SLE was observed between seizures and migraine (p < 0.001) and between headache and disease activity (p < 0.001). When comparing the presence of migraine to clinical and laboratorial results we observe a significant association with Raynauds phenomenon (p < 0.05), LE cels (p < 0.05), antifosfolypid antibodies (p < 0.001). Conclusion: Migraine was more prevalent in SLE than in the control groups. The positive association between migraine and seizures and a higher score at SLEDAI could be related to a greater CNS involvement in these patients. In our study, migraine was associated to antiphospholipid antibodies. References: Omdal R, Mellgren SI, Husby G. Clinical neuropsychiatric and neuromuscular manifestations in systemic lupus erythematosus. Scand J Rheumatol. 1988;17:113–17 Adelman DC, Saltiel E, Klinenberg JR. The neuropsychiatric manifestations of systemic lupus erythematosus: an overview. Semin Arthritis Rheum. 1986;15(3):185–99